Inducing Breach of Contract, Conversion and Contract as Property - LEE, Pey Woan (Institutional Knowledge at Singapore Management University, 2009)
This article seeks to understand contractual rights through an examination of the possible ‘property’ content in contracts in the context of the inducement tort and conversion. It argues that, contrary to popular perception, contracts and property are different shades of a similar phenomenon. Not being a reified ‘thing’ with stable features and structure, property is a relative rather than an absolute concept. To determine whether the holder of an intangible resource ought to be conferred with ‘property’ or exclusive control of access to such resource, one has to evaluate the relevant practical, legal and moral considerations. Applied to the context of inducing breach of contract and conversion, this analysis demonstrates that a contractual right is in fact a composite collection of distinct interests and each tort may be protective of one or more of such interests. Thus, liability is imposed for inducing breach of contract because tort law recognizes the promisee’s exclusive right to the peremptory status of the promisor’s promise. On the other hand, the wrongfulness of converting a contract lies in the usurpation of a contracting party’s control, or the exclusive entitlement to decide whether and how to exercise her rights under the contract.